THE EFFECTS OF EDUCATION LEVEL ON RADIATION PROFESSIONALS’ KNOWLEDGE AND IMPLEMENTATION OF ALARA PRINCIPLES FOR OCCUPATIONAL RADIATION PROTECTION - Jawidah Adiba Kamarolzeman; Ivy June Boniface; Azlan Safian; Nur Maizatul Azra Mukhtar; Ainorkhilah Mahmood; Aina Nafisya Suhaimi; Nur Fatma Husna Noor Azman (Journal of Islamic, Social, Economics and Development, 2024)
The risk of radiation hazard may be increased by either a high exposure to primary radiation or by low doses of radiation scattered from the patient’s body. As a self-control mechanism and protection against radiation hazards, the ALARA concept and understanding of the principle itself are necessary. Time, distance, and shielding are the three fundamental precautionary measures that the ALARA employs to help lessen the hazardous effects of radiation. According to that, a final-year student at the University Technology of MARA, Penang Branch, Malaysia, conducted a survey to investigate the effect of education level on perception and awareness of radiation protection and safety among radiation workers. The survey was designed in Google Forms and distributed to a number of public and private institutions and industries that used ionizing radiation. This survey had 84 respondents, with only 78 having their data further analyzed after the validation process, yielding a response rate of 52.6% men (n = 41) and 47.4% women (n = 37). Only fifteen of the 29 designated questions were chosen for further analysis and discussion in this paper. Only one of the seven (7) variables, time spent with radiation sources or procedures, provided a statistically significant difference in group means, and the p-value for this factor (0.013) is less than the α-value (p0.05), when compared to the other six (6) variables (p>0.05). Thus, it can be concluded that workers' educational attainment had no bearing on their knowledge, awareness of, or adherence to ALARA.